Effect of Partial Replacement of Soybean Meal with Fish Silage on the Performance of Broilers on Conventional Starter and Finisher Diets - Mohammed , Aphzal; Ramlall, Harry; Edwards, Andell; Sieuchand, Shenese; Khan, Angelisah (International Journal of Poultry Science, 2016)
Four batches of broilers (40 birds/batch) were randomly allocated to diets in which some of the soybean meal (control) was replaced with a dry mixture of acid fish silage and wheat middlings (experimental). The initial weight of the broilers was taken when the birds were 10 days old and they were fed until they were 56 days of age. The average final weight (kg) was taken when the birds were 2.254 and 2.194 and, over 46 days, 2.014 and 1.944 in the control and experimental diets, respectively and were significantly (p>0.05) different. The average daily gains (g) over 56 and 46 day periods were 44, 43, 44 and 42 for the control and experimental diets, respectively and were significantly (p<0.05) different. The feed conversion efficiency of 2.06 and 2.20 g for the control and experimental diets, respectively, were significantly (p>0.05) different. The average daily gain and Feed Conversion Ratios were higher (p<0.05) for the conventional diet compared to the acid silage replacement diet.